2014
DOI: 10.1097/fjc.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits Phenotypic Switching of Neointimal Vascular Smooth Muscle Cells After Balloon Injury Through Blockade of Notch Pathway

Abstract: The results indicate that RSV can attenuate phenotypic switching of VSMCs after arterial injury through inhibition of the Notch pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Here, we showed that resveratrol inhibited AngII-induced proliferation and migration in A7r5 cells. These results are consistent with previous studies that demonstrated the anti-proliferative effects of resveratrol on VSMC proliferation following serum (24) or PDGF-BB (28) stimulation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, we showed that resveratrol inhibited AngII-induced proliferation and migration in A7r5 cells. These results are consistent with previous studies that demonstrated the anti-proliferative effects of resveratrol on VSMC proliferation following serum (24) or PDGF-BB (28) stimulation.…”
Section: Discussionsupporting
confidence: 93%
“…Changes in VSMC proliferation and migration are largely reported to contribute to neointimal hyperplasia and restenosis after angioplasty (23). It has been demonstrated that environmental factors, such as PDGF, endothelin, transforming growth factor, and inflammatory mediators, can induce synthetic smooth muscle cell phenotypic differentiation (24). AngII is a well-documented activator of VSMC proliferation and migration, which promotes atherosclerosis and vessel stenosis (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…57 The phenotype switch of SMC from contractile to synthetic phase also impairs vessel contraction. In our experiments, gingerol pretreatment significantly prevented balloon injury-induced reduction in PE-mediated vessel contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Both in rat aortic subintimal macrophages and in in vitro-differentiated macrophage cell diosgenin, a phytosteroid sapogenin extracted from the tubers of Dioscorea wild yam suppresses the nuclear translocation of NICD [302]. Resveratrol can attenuate neointimal VSMC hyperplasia in rats, following balloon injury, through a mechanism that involves inhibition of the Notch signaling [303]. Activation of Notch signaling reduces myocardial ischemia reperfusion injury (MI/RI), by activating key components of survival pathways, namely, PI3K-Akt, NOS, and mitochondrial K + -ATP (mitoKATP) channels [231]; BBR, polydatin, and 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside upregulate Notch-1/HES1 signaling attenuating myocardial apoptosis both in cultured cardiomyocytes and in rats subjected to MI/RI [304][305][306].…”
Section: Nutraceuticals Acting Through the Notch Pathwaymentioning
confidence: 99%